DESIGN AND BUILDING OF ADJUSTABLE OIL FILLER AUTOMATIC COOKING OIL MEASURING FLOW SENSOR METHOD BASED ON ARDUINO NANO - Perangin Angin, Despaleri; Situmorang, Maizer; Samosir, Gilson Manahara (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Cooking oil is one of the household needs, where its use is very embedded among the wider community, therefore the circulation and distribution of cooking oil plays an important role, to help its distribution through MSME businesses, whether traders, the author designed an automatic cooking oil measuring tool with the research title Design Build an adjustable oil filler that measures automatic cooking oil based on Arduino nano. In the research the tool is running normally, using Arduino as the main component and the flow sensor inputs the tool data from the amount of liquid output, in the final result of this research the tool produces data values ​​with output accuracy values 99.44% data taken from comparing the volume output of the instrument and Matt Glass measuring instrument as a reference for the original volume and the endurance test obtained a value of 93% with 30 trials with 2 failed trials. Therefore, it can be concluded that this adjustable oil filler tool functions well and can be used. Keywords: Arduino cooking oil meter, Adjustable cooking oil oil filler Keywords:   Penakar minyak Goreng Arduino, Oil filler Adjustable Minyak Goreng